Medical diagnosis: a crucial problem in the 21st Century - Emiliano Diez y Martínez de la Cotera (Medisur)
A review of the history of medicine was conducted in order to evaluate the evolution of “diagnosis” and it was concluded that it was firstly defined by Hippocrates almost two thousand and five hundred years ago. The evolution of the concept is analyzed according to the scientific developments of each epoch. Different methods and their stages to obtain a diagnose are exposed. Similarities of the scientific and clinical methods are analyzed, as a necessary procedure for a good medical diagnosis. Different forms of doctor patient relationship are described, as an essential step for an accurate diagnosis. Medicine is approached as a totally uncertain, probabilistic science aimed to a final diagnosis. It is also emphasized that scientific and technological development bring us adequate tools for taking better decisions in order to facilitate medical diagnosis and its confrontation, not only in a single patient but in the analysis of its effectiveness in groups and communities. Basic pieces of advice are provided on how to obtain diagnoses in daily medical practice. Finally, two patterns in medical procedures are exposed: the Galenic and the Hippocratic.